KOMUNIKASI DAKWAH PADA FITUR VIDGRAM @ULAMA.NUSANTARA: Studi Deskriptif Menggunakan Teori Pertukaran Sosial - Muhammad Diak Udin (Indonesian Journal of Islamic Communication, 2021)
Abstrac: This study aims to review two things. First: How is Instagram used as a da’wah medium by the @ulama.nusantara account? Second: What is the background for the @ulama.nusantara account to choose videogram as a medium for delivering its da'wah message? This study used a qualitative descriptive method using social exchange theory as its approach to obtain these answers. The results of this study are: First; Consistency of the @ulama.nusantara account in producing and distributing da'wah content through several processes, including 1) Selecting sources and content; 2) Producing content in the form of quotes, narrations, and videos; 3) Share products on the @ulama.nusantara account page. Second: The idea of ​​making videogram as a priority scale in delivering da'wah messages is based on three main reasons, namely: 1) More Varied; 2) Limited Human Resources; 3) Level of Effectiveness. This study confirms the assumption of social exchange theory, which states that every relationship built between individuals is based on profit and loss motives.